Pengaruh Pengetahuan, Lingkungan Sosial, dan Ketersediaan Fasilitas Terhadap Minat Berinvestasi Mahasiswa di Pasar Modal (Studi Kasus pada Mahasiswa FEB dan FIA Universitas Islam Malang Angkatan 2019) - Chulukiyah, Husnul; Mawardi, M. Cholid; Nandiroh, Umi (Universitas Islam Malang, 2023)
During the Covid-19 pandemic, local investors increased drastically. The Indonesian Stock Exchange (IDX) notes that investors until June 2022 are dominated by millennials and gen z. This shows that Indonesian people are starting to realize the importance of investing. The purpose of this study was to determine the factors that influence the interest of FEB and FIA Unisma students. This study uses the theory of planned behavior because it explains a person's intention to do something. The research method applied is multiple linear regression analysis. The conclusions from this study are that the variables of knowledge, social environment, and facilities have a simultaneous effect on investment intentions, and each has a partial effect on investment intentions. For future researchers, they can add other variables that have not been studied, such as minimum capital, return, risk, understanding of financial literacy, etc.Keywords: Knowledge, social environment, facilities, interest, investment, capital market